COMICIDADE E PICARDIA NA LITERATURA DE CORDEL: AS PROEZAS DE MARIA BESTA SABIDA - Silva, Carlos Magno Vitor da (2008)
This research have of principal theme the study of the comic-picaresque cycle in the cordel literature (string literature), based in the four leaflets that narrate the achievements of Maria Besta Sabida, of the cordel poet rooted in Feira de Santana, Ant?nio Alves da Silva, discussed under the interdisciplinary approach, involving literary theory, the aesthetics of laughable and studies popular culture. The specific objective of this work of research is: a)chart to the biographical profile of Ant?nio Alves da Silva; b) analyze to the nature of popular comicality, especially taking into account its aesthetic formatively and its resources linguistic-literary expression and c) exam to the specifically picaresque women, with cronotopo particularly adapted to the northeastern Brazilian reality. The position taken in this dissertation, in that respect, took the view that Maria Besta Sabida is a legitimate Brazilian picaresque, in a line of continuity of the Iberian matrix picaresque, of the centuries XVI and XVII. As appendix, will be presented a (new) of all works of AAS, catalogued the second thematic classification of Ariano Suassuna.